The Norwegian Society for Pharmacoepidemiology - Angela Lupattelli; Øystein Karlstad; Anders Engeland; Lars Småbrekke; Kristine Olsen; Aina Øvrebust; Marit Waaseth (Norsk Forening for Epidemiologi, 2021)
-